Charting The Development and Intersection of Agrarianism, Transcendentalism and Ecocriticism - Kristiawan Indriyanto; Desca Angelianawati (Unipdu Jombang, 2023)
AbstractThis paper charts the emergence of agrarianism as a philosophical thought, situates its development within other ideas such as Romanticism and Transcendentalism, and how agrarian thought intertwined with ecocritical literary analysis. The premise of this study is that within the current state of environmental crisis and degradation, the insight from agrarianism can provide an alternative environmental imagination to reconsider the position of humanity in the wider world. This study applies intellectual history as the framework on how the concepts and theories interacted and influenced other social/cultural/intellectual developments. Agrarianism celebrates rural life and agriculture as a response to industrialization, championed by thinkers like Emerson and Thoreau, who see it as a path to a more meaningful existence. It then examines how agrarianism intersects with ecocriticism, an environmental literary perspective that emerged in the 1960s. Agrarianism contributes significantly to ecocriticism, particularly in its critique of industrialization, exemplified by Rachel Carson's